Causal relationship between immune cells and neurodegenerative diseases: a two-sample Mendelian randomisation study - Tang, Chao; Lei, Xiaoyang; Ding, Yaqi; Yang, Sushuang; Ma, Yayu; He, Dian (Frontiers in Immunology, 2024)
There is increasing evidence that the types of immune cells are associated with various neurodegenerative diseases. However, it is currently unclear whether these associations reflect causal relationships.To elucidate the causal relationship between immune cells and neurodegenerative diseases, we conducted a two-sample Mendelian randomization (MR) analysis.PD, 6 different types of immune cells have potential causal relationships with ALS, and 6 different types of immune cells have potential causal relationships with MS.Our study, through genetic means, demonstrates close causal associations between the specific types of immune cells and AD, PD, ALS and MS, providing useful guidance for future clinical researches.